Advokasi World Animal Protection Terhadap Permasalahan Kesejahteraan Beruang Melalui China’s Local Office Ditinjau Dari Hukum Organisasi Internasional - Manurung, Hadonia Lazarus; Jayakusuma, Zulfikar; Diana, Ledy (Balobe Law Journal, 2024)
Introduction: Transnationalism era, there has been a structured change in various dimension of International relations, include the actor which implies that the state is not the only capable one to influencing global developments. This shift strengthens INGO’s role as a part of international organization. Their advocacy plays an important role in bear welfare issues at China’s Bears Bile Industry.Purposes of the Research: This article aims to review World Animal Protection’s competences as a jurisdiction personality through its advocacy agenda on Bears bile industry in China.Methods of the Research: This article is written by utilizing normative legal research by focusing on synchronization of World Animal Protection’s advocacy effort and balances to Chinese administration also law through historical and descriptive methods.Results of the Research: World Animal Protection’s advocacy has conformed to the general legal principles of environmental by utilizing the ethics of biocentralism, which entirely aimed to the mission of saving bears. However, the advocacy launched against China’s bear bile industry should be against international organization law based on the absence of permanent secretariat in China. This action may be due to the organization’s lack of compliance to naturalize its administration and laws in China. Therefore, the resulting effect tends to be puzzling because it doesn’t show a significant and measurable impact when compared to the other advocacy through similar issues.